2022
DOI: 10.3390/land11050629
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Variation and Mechanisms Causing Spatial Differentiation of Ecosystem Services in Ecologically Fragile Regions Based on Value Evaluation: A Case Study of Western Jilin, China

Abstract: The concept of Ecosystem Service Value (ESV) is indispensable when balancing the need for economic development and ecological protection, because it can clarify the ecological assets and values provided by a region. The study of spatio-temporal variation of ESV in ecologically fragile regions is helpful when attempting to restore regional ecological function. Taking the ecologically fragile area in Western Jilin as an example, this paper analyzes the spatial distribution and spatial-temporal evolution characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, the population growth issues that are connected with socioeconomic development may reflect the contradiction between human activities and human well-being [ 4 ]. Under this context, ecosystem service value (ESV) is indispensable when balancing the need for food production and ecological protection because it can clarify the ecological assets and values provided by a region [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the population growth issues that are connected with socioeconomic development may reflect the contradiction between human activities and human well-being [ 4 ]. Under this context, ecosystem service value (ESV) is indispensable when balancing the need for food production and ecological protection because it can clarify the ecological assets and values provided by a region [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that the ESV often varies in terms of its temporal and spatial characteristics [ 34 , 35 ]. For example, Shang et al found that the interaction between the NDVI and soil types had the most substantial impact on the spatial differentiation of the IESV in the study area, with an explanatory power of 21.95% [ 5 ]. Therefore, it is essential to carry out some studies in different regions to analyze changes in the ESV.…”
Section: Introductionmentioning
confidence: 99%